Job Satisfaction of Secondary School Teachers: A Case Study on Chuadanga District - Mohammad Jamal Uddin, Md. Rashedul Islam & Nil Kamal Saha (Academic Journal on Business Administration, Innovation & Sustainability, 2021)
Education is recognized as one of the most powerful aspects of human development and poverty reduction. There is a wise saying that “Education is the backbone of a nation”. Bangladesh government has taken various measures to educate its population in recognition of the potentials of education for its nation. Since 1971s, Bangladesh government has recognized education as one of the top priority areas. Job satisfactions of secondary school teachers mean teachers are satisfied or dissatisfied in the job as a teacher in the secondary school. For this purpose determine the satisfaction level. In this case researcher prepared a structured questionnaire. Through this questionnaire data are collected. In this collected data determine personal and job related factors. Calculating these determine the level of satisfaction and dissatisfaction level. Overall the most of the secondary school teachers are dissatisfied in their present job. Though the govt. secondary school teacher are satisfied with most of the factors but non-govt. secondary school teachers are dissatisfied with most of the factors.